Examining the Mind Mapping Model in Mathematics Learning for Elementary School Students: Self-Efficacy and Motivation - Novitasari Widyastuti; Herwin (Jurnal Ilmiah Sekolah Dasar, 2024)
The challenges of student learning in the 4.0 era must be balanced with mastery of 21st century skills. Mastery of skills must be balanced with students' mental maturity. The mental maturity of student learning can be developed by applying an effective learning model. The mind mapping learning model has various advantages for shaping the maturity of students' thinking patterns. This research was conducted with the aim of examining the application of the mind mapping model for self-efficacy and student motivation. The research subjects were 10 grade IV elementary school students. This research method is a quasi-experimental study that compares pretest and posttest values. The data collection techniques used were observation and interview techniques, which were converted into a value of 1–100. Data analysis was carried out, both quantitatively and qualitatively. The results of the study showed that there was an increase in pretest self-efficacy to posttest 1 of 12.4 points, and an increase in posttest 1 to posttest 2 of 9.4 points. The results of observing student motivation at the pretest to posttest stage were 10.8 points, and a significant increase from the results of posttest 1 to posttest 2 was 23.6 points. The research findings are that the mind mapping model increases student self-efficacy, increases student motivation, and has significant advantages for elementary school students. An interesting finding is that students' mentality can be more stable with the application of mind mapping, with indications of independence, initiative, courage, and a change in perception of mathematics.